Comparing the linkages between carbon components and soil aggregates in vegetable fields to continuous input of different carbon sources. - Yuan Yang Peng; Jiang Ling Huang; Yan Qin Peng; Yin Peng; Shi Xiong Li; Xi la Tu Da Bu (PLoS ONE)
Aims To address the issue of declining soil organic carbon (SOC) in vegetable fields, this study investigated the effects of continuous input of different carbon sources on soil carbon pool dynamics. Methods A five-year field plot experiment was conducted to analyze the impact of organic fertilizer, biochar, and their combined application on soil organic carbon components, aggregate stability, and carbon pool characteristics. Results The continuous application of biochar and organic fertilizer significantly increased the content of soil organic carbon components. Organic fertilizer contributed more actively to labile organic carbon fractions, whereas biochar primarily supplied stable organic carbon. All treatments enhanced the proportion of macroaggregates (>0.25 mm) and improved aggregate stability, with organic fertilizer exhibiting superior effects compared to biochar. Organic fertilizer also promoted organic carbon sequestration in aggregates by enriching readily oxidizable organic carbon (ROC) and water-soluble organic carbon (DOC). In contrast, biochar application significantly increased inert organic carbon (IOC), leading to higher total SOC compared to organic fertilizer alone. Carbon pool characteristic indices improved significantly under continuous biochar and organic fertilizer application. Organic fertilizer treatment showed a higher carbon pool activity index, while biochar outperformed in other indices. The combined application yielded the most favorable results. Correlation analysis revealed that soil aggregate stability was significantly associated with DOC and microbial biomass carbon (MBC). Both biochar and organic fertilizer enhanced soil available nutrient content, which increased dynamically over time. Principal component analysis confirmed that the combined application of organic fertilizer and biochar was most effective for soil carbon sequestration and fertility improvement. Conclusion Biochar and organic fertilizer differentially influenced soil organic carbon composition. Organic fertilizer improved carbon pool characteristics by mediating macroaggregate formation through labile organic carbon (e.g., DOC and MBC), while biochar contributed directly to carbon sequestration due to its inert and stable nature. Their combined application synergistically enhanced the formation and stability of soil macroaggregates, improved soil carbon pool characteristics, and optimized nutrient availability in vegetable fields. This version improves clarity, conciseness, and flow while maintaining scientific accuracy. Let me know if you'd like any further refinements!.